Socialist aberrations of Donbas and conservative modernization of Russia - Dodonova, Vira (Skhid, 2015)
The article analyzes the political situation in the East of Ukraine, studies the causes of armed conflict in the region. The purpose of this article is to assess the mass public expectations of new state formations in the east of Ukraine with regard to socialist transformation and correlation of these expectations with the strategic installations ruling in Russia. The first semantic unit of the article substantiates that Donbass in its current form is a product of Soviet industrialization, and therefore the mass consciousness is characterized by nostalgia for the recent past. It is with the socialism that calls for social justice, equality, democracy, against theft, corruption, oligarchs and private property are connected. Although these provisions are not recorded under the heading of "building socialism in the DNR and LNR", residents of these political formations in all their undertakings are inclined to see the very socialist component. The self-government is forced to reckon with the mood of the masses, sharing socialist rhetoric at least "in the outer form". The article analyzes the program of socio-political movement "New Russia Party". The second semantic unit of the article studies the strategy of conservative modernization in Russia, which includes: first, consolidation of the elites; second, uncompromising struggle with the moral justification for violations of the written law; and third, movement towards realistic legislation. The course for conservative modernization does not imply socialist methods in public administration and functioning of the economy. Thus, there is a real contradiction between the political expectations of some residents of the DNR and the LNR for the restoration of socialism and the real transformations in Russia itself, which have no relation to the socialist transformation.